The Effect of Quizizz and Learning Independence on Mathematics Learning Outcomes - Khasanah, Khasanah; Lestari, Anugrah (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2021)
The purpose of this study was to determine the effect of Quizizz media and independent learning on mathematics learning outcomes on the subject of derivative functions, with worksheet media as the control variable. They rely on an experimental method with the two-way analysis of variance (ANOVA) and the Tukey analysis. The results showed a significant difference where the mathematics learning outcomes of class XI students who were taught using Quizizz media were higher than those taught using worksheet media. There is an interaction of learning media with independent learning on mathematics learning outcomes of class XI students. The mathematics learning outcomes of the eleventh-grade students who have high learning independence and were taught using this media are higher than the learning outcomes of students who were taught using worksheets. This study concludes that there are Quizizz media's effect and learning independence on mathematics learning outcomes based on the analysis results. This study's results have implications for choosing Quizizz media and the relationship between learning media interactions with students' learning independence.